MiR-320b and miR-320d as Biomarkers to Predict and Participate in the Formation of Platinum Resistance in Ovarian Cancer Patients - Liu, Yuan-Yuan; Zhao, Ren-Feng; Liu, Chao; Zhou, Jie; Yang, Liu; Li, Li (Frontiers in Oncology, 2022)
Patients with ovarian cancer who receive platinum-based chemotherapy typically develop platinum resistance, which leads to tumor recurrence and mortality. Therefore, finding the underlying mechanisms and biomarkers is critical. A total of 51 platinum-resistant and 70 platinum-sensitive ovarian cancer patients were enrolled in this study. We examined the GSE131978 dataset in the National Center for Biotechnology Information (NCBI) Gene Expression Omnibus database for differentially expressed long non-coding RNAs and messenger RNAs (mRNAs) between platinum-resistant and platinum-sensitive patients and completed a microRNA chip analysis. After filtering by Pearson correlation analysis, the competitive endogenous RNA (ceRNA) networks were subsequently constructed. Then, the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology enrichment analyses about mRNAs in ceRNA networks were accomplished. More crucially, we demonstrated the differentially expressed microRNAs using quantitative real-time PCR and fluorescence in situ hybridization. The feasibility of microRNAs as biomarkers to predict platinum resistance and tumor recurrence was assessed using the receiver operating characteristic curve and survival analysis. MiR-320b and miR-320d exhibited high area under the curve values of 0.757 and 0.702, respectively. In our study, ceRNA networks including miR-320b and miR-320d probably provided novel insights for platinum resistance in ovarian cancer patients.